Psychological Well-Being of Pre-Service Training Teachers - Rachmawati, Indriyana; Lidyasari, Aprilia Tina (Jurnal Kajian Bimbingan dan Konseling, 2023)
The recent statistic suggests the average psychological well-being of Indonesian citizens, including the pre-service training teacher, represents their capacity to overcome future challenges. Excellent psychological well-being is crucial for pre-service training teachers, especially for providing a comfortable learning situation for students and engaging in effective communication with students. This study investigates the psychological well-being of pre-service training teachers. Thus, this study adopted survey techniques with descriptive data analysis. The data were collected from 44 teachers selected by purposive sampling. The criteria for selecting research participants were currently taking pre-service teacher education, elementary school teachers, and willingness to participate in this study. Data were collected using a psychological well-being scale. The results of the analysis showed high and exceedingly high psychological well-being of pre-service training teachers. However, the majority of participants had low scores in the aspect of improving self-quality over time, and some of them presented remarkably low scores